Analysis Of Consumer Loyalty Which Servicescape And Lifestyle Influenced With Consumer Satisfaction As A Mediating Variable - Kezia Lidya Imanuella; Aris Budiono (International Journal of Economic Research and Financial Accounting, 2023)
The purpose of this study is to carry out an influence analysis variable Servicescape (X1), Lifestyle (X2), satisfaction (Y1), and consumer loyalty (Y2).as the dependent variable, simultaneously or partially in the contexts of business in the culinary field. In this study, the data was developed using a Likert scale. The respondent population of 100 people. The number of respondents was taken from 30 people for validation and reliability tests. This study uses quantitative methods using path analysis. SPSS 20 is used for data analysis with two substructures in measurement. Substructure 1 The Effect of Servicescape and Lifestyle on Consumer Satisfaction. Substructure 2, The Influence of Servicescape, Lifestyle, and Consumer Satisfaction on Loyalty. The results of this research state that Servicescape has a significant effect on customer satisfaction, Lifestyle does not affect customer satisfaction, Servicescape has no significant effect on customer satisfaction, Lifestyle has no significant effect on customer loyalty, consumer satisfaction has an effect on customer loyalty, Servicescape has no significant effect on consumer loyalty through customer satisfaction, Lifestyle has an effect on customer loyalty through consumer satisfaction.